Structural-Functional Analysis of the Genes, Encoding Biosynthesis of Mannose-Sensitive Hemagglutinating Pili of Adhesion in Different Vibrio cholerae El Tor Strains - N. A. Plekhanov; S. P. Zadnova (Проблемы особо опасных инфекций, 2016)
Objective of the study is to conduct comparative structural and functional analysis of the genes, encoding biosynthesis of man-nose-sensitive hemagglutinating pili in typical V. cholerae El Tor strains and genovariants. Materials and methods. Utilized were typical and genetically altered strains of cholera vibrio, biovar El Tor, isolated in the territory of the Russian Federation between 1970 and 2012 from ambient environment objects and from patients. Applied were microbiological and molecular-genetic methods, as well as analysis of the data on the whole genome sequencing. Results and conclusions. Using PCR assay the presence of mshA gene, encoding basic sub-unit of MSHA pili, has been detected in all of the tested strains. Comparative analysis of the nucleotide sequence of the genes, included into msh cluster, has revealed identity of the nucleotide sequence of mshA gene, both in typical V. cholerae strains and genovariants. Thereat, in strains of genovariants, isolated at the time of their emergence (1988, 1993, 1994), the structure of the other genes in msh operon is identical to typical El Tor vibrios. At the same time, since 1997, in strains of V. cholerae El Tor genovariants, in the sequence of the genes, involved in the assembly and secretion of MSHA pili, identified have been the SNPs, which do not influence biosynthesis of these pili, but their occurrence, probably, was due to adaptation of the genovariant strains to varying living conditions.